Comparative FAIRE-seq Analysis Reveals Distinguishing Features of the Chromatin Structure of Ground State- and Primed-Pluripotent Cells. (22nd January 2015) - Murtha, Matthew; Strino, Francesco; Tokcaer-Keskin, Zeynep; Sumru Bayin, N.; Shalabi, Doaa; Xi, Xiangmei; Kluger, Yuval; Dailey, Lisa
Abstract: Both pluripotent embryonic stem cells (ESCs), established from preimplantation murine blastocysts, and epiblast stem cells (EpiSCs), established from postimplantation embryos, can self-renew in culture or differentiate into each of the primary germ layers. While the core transcription factors (TFs) OCT4, SOX2, and NANOG are expressed in both cell types, the gene expression profiles and other features suggest that ESCs and EpiSCs reflect distinct developmental maturation stages of the epiblast in vivo. Accordingly, "naïve" or "ground state" ESCs resemble cells of the inner cell mass, whereas "primed" EpiSCs resemble cells of the postimplantation egg cylinder. To gain insight into the relationship between naïve and primed pluripotent cells, and of each of these pluripotent states to that of nonpluripotent cells, we have used FAIRE-seq to generate a comparative atlas of the accessible chromatin regions within ESCs, EpiSCs, multipotent neural stem cells, and mouse embryonic fibroblasts. We find a distinction between the accessible chromatin patterns of pluripotent and somatic cells that is consistent with the highly related phenotype of ESCs and EpiSCs. However, by defining cell-specific and shared regions of open chromatin, and integrating these data with published gene expression and ChIP analyses, we also illustrate unique features of the chromatin of naïve and primed cells. Functional studies suggest that multiple stage-specific enhancers regulate ESC- or EpiSC-specific gene expression, and implicate auxiliary TFs as important modulators for stage-specific activation by the core TFs. Together these observations provide insights into the chromatin structure dynamics accompanying transitions between these pluripotent states. Stem Cells   2015;33:378–391